2020
DOI: 10.1186/s12874-020-00928-w
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of core outcome sets and their ‘mapping’ onto real-world data using prostate cancer as a case study

Abstract: Background: A Core Outcomes Set (COS) is an agreed minimum set of outcomes that should be reported in all clinical studies related to a specific condition. Using prostate cancer as a case study, we identified, summarized, and critically appraised published COS development studies and assessed the degree of overlap between them and selected real-world data (RWD) sources. Methods: We conducted a scoping review of the Core Outcome Measures in Effectiveness Trials (COMET) Initiative database to identify all COS st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Importantly, for some registries, mostly in Scandinavian countries, data linkage is possible and, therefore, even if registries do not directly include economic outcomes, these can be obtained and/or expanded through other administrative data sets. It is very important to enable as much as possible data linkage (20), to avoid enlarging existing data sets with additional variables, which is expensive in terms of costs and time, and to capitalize on existing sources.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, for some registries, mostly in Scandinavian countries, data linkage is possible and, therefore, even if registries do not directly include economic outcomes, these can be obtained and/or expanded through other administrative data sets. It is very important to enable as much as possible data linkage (20), to avoid enlarging existing data sets with additional variables, which is expensive in terms of costs and time, and to capitalize on existing sources.…”
Section: Discussionmentioning
confidence: 99%
“…Patients, as well as health care professionals administering PROMs, are unlikely or unable to spend a considerable amount of time filling out questionnaires. In a recent mapping exercise from COS studies in prostate cancer to existing real world data sources, we found that self-reported outcome measures are a dimension not typically covered in routinely collected data sources (58). However, the current technological landscape would allow for a wide scale, standardized, continuous collection of PROMs (2).…”
Section: Discussionmentioning
confidence: 99%
“…Across many clinical areas including urology, patient-reported outcomes and clinical outcomes are reported inconsistently, with variability in definitions and measurement, for instance in the settings of localised prostate cancer and bladder cancer [8] , [9] , [10] . This makes it very difficult to compare and synthesise outcomes to improve guidelines to better direct and support patients and clinicians during treatment decision-making and ultimately improve results in clinical practice [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%